Sudden Deaths Due to Choking - RanjanNayak, Soumya; Jena, Manoj Kumar; Panda, Bibhuti Bhusan; Singh , Purnima (Journal of Indian Academy of Forensic Medicine, 2015)
Death due to accidental choking is observed in all age group and small children below 4 years of  age are the common victims. Choking is commonly seen in children when objects such as small toys,  table tennis ball and coins are placed in mouth and inhaled. Food is the most common cause of choking  and food which is the life provider can become an asphyxiating agent at times. Children younger than one  year of age are more likely to aspirate food, whereas older children tend to choke on non-food items.  Aspiration of gastric contents is common in individuals with a decreased level of consciousness in drug  overdose and during anaesthesia. The risk of aspiration is high after removal of an endotracheal tube  because of residual effects of sedative drugs, the presence of a nasogastric tube, swallowing dysfunction  related to upper airway sensitivity, glottic injury and laryngeal muscular dysfunction. Aspiration can  present with acute respiratory distress but in many elderly individuals, it is silent. We hereby report cases  of sudden death due to choking which were brought to our mortuary for autopsy.
Keywords: Choking; Sudden death; Aspiration; Autopsy